2021
DOI: 10.3390/ma14133586
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lithium-Ion Capacitor Based on a NiO-rGO Composite

Abstract: Lithium-ion capacitors (LICs) have been widely explored for energy storage. Nevertheless, achieving good energy density, satisfactory power density, and stable cycle life is still challenging. For this study, we fabricated a novel LIC with a NiO-rGO composite as a negative material and commercial activated carbon (AC) as a positive material for energy storage. The NiO-rGO//AC system utilizes NiO nanoparticles uniformly distributed in rGO to achieve a high specific capacity (with a current density of 0.5 A g−1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Table shows the comparison of the Li-ion supercapattery performances reported for the single oxide-based supercapacitor and the present work. It is seen that energy density in the range of 90–140 W h kg –1 and power density in the range of 98–1390 W kg –1 are represented in the literature. In the present work, high specific energy of 212 W h kg –1 at a specific power of 529 W kg –1 was obtained. Further, the non-aqueous device underwent rate capability assessment at various current densities the same as before, and the corresponding specific capacities were determined using eq .…”
Section: Results and Discussionsupporting
confidence: 53%
“…Table shows the comparison of the Li-ion supercapattery performances reported for the single oxide-based supercapacitor and the present work. It is seen that energy density in the range of 90–140 W h kg –1 and power density in the range of 98–1390 W kg –1 are represented in the literature. In the present work, high specific energy of 212 W h kg –1 at a specific power of 529 W kg –1 was obtained. Further, the non-aqueous device underwent rate capability assessment at various current densities the same as before, and the corresponding specific capacities were determined using eq .…”
Section: Results and Discussionsupporting
confidence: 53%
“…Geerthana Mummoorthi et al, researched that the ternary composite α-Fe 2 O 3 /NiO/rGO has shown a specific capacitance of 747 F/g@ a current density of 1 A /g in a 6 M KOH [14]. Qi An et al, prepared NiO-rGO, NiO nanoparticles uniformly distributed in rGO to achieve a high specific capacity at current density of 0.5 A /g [15].O. C. Pore et.al., synthesised NiO/rGO composite achieved the highest specific capacitance of 727.1 F/g at 1 mA cm −2 current density and showed good cyclic stability of about 80.4% over 9000 cycles [16].…”
Section: Introductionmentioning
confidence: 99%